THE EFFECT OF ASSET STRUCTURE, PROFITABILITY, COMPANY SIZE, AND COMPANY GROWTH ON CAPITAL STRUCTURE (The Study of Manufacturing Companies Listed on the IDX for the Period 2013 - 2017) - Ariyani, Hilma Faza; Pangestuti, Irene Rini Demi; Raharjo, Susilo Toto (JURNAL BISNIS STRATEGI, 2018)
The purpose of this study was to determine and examine the effect of asset structure, profitability, firm size and company growth on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013 â€“ 2017. The sampling method used was purposive sampling that was 52 companies in the criteria. Data obtained from the Financial Reports and Performance Reports published in the Indonesian Capital Market Directory (ICMD). The analytical tool that used is multiple regression. Hypothesis testing is done by the F test, t-test and determination coefficient. For the classical assumption, the test is done by the normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The analysis of asset structure has a positive effect on the capital structure and not significant to the capital structure, profitability has a negative and significant effect on the capital structure, the size of the company has a positive and significant effect on the capital structure, and the companyâ€™s growth has a negative and significant effect on the capital structure.Â